Equal-area projection: spheroid to sphere to plane - Pantelidis, Lysandros (My University, 2013)
An accurate method for the equal-area projection from spheroid to plane is proposed. The points of interest are first projected from the spheroid to an equivalent sphere, that is, to a sphere of equal area. Then, the points of the equivalent sphere are projected onto the surface of a circumscribing cylinder (cylindrical equal-area projection) following the standard mapping procedure of mapping the sphere to the plane.
Keywords: Equal-area projection; Spheroid to sphere; Surface area of revolution; Map projection